Teaming up with large R&D investors: Good or bad for knowledge production and diffusion? - Sara Amoroso; Simone Vannuccini (European Commission, Joint Research Centre (JRC), 2019)
The participation of top R&D players to publicly funded research collaborations is a common yet unexplored phenomenon. If, on the one hand, including top R&D firms creates opportunities for knowledge spillovers and increases the chance for a project to be funded, on the other hand, the uneven nature of such partnerships and the asymmetry in knowledge appropriation capabilities could hinder the overall performance of such collaborations. In this paper, we study the role of top R&D investors in the performance of publicly funded R&D consortia (in terms of number of patents and publications). Using a unique dataset that matches information on R&D collaborative projects and proposals with data on international top R&D firms, we find that indeed teaming up with leading R&D firms increases the probability to obtain funds. However, the participation of such R&D leaders hinders the innovative performance of the funded projects, both in terms of patents and publications. In light of this evidence, the benefits of mobilizing top R&D players should be carefully leveraged in the evaluation and design of innovation policies aimed at R&D collaboration and technology diffusion.
Keywords: L24; L25; O33; 330; Collaboration; public funding; innovation performance; appropriability; top R&D investor